Long‐Lived, Visible‐Light‐Excited Charge Carriers of TiO2/BiVO4 Nanocomposites and their Unexpected Photoactivity for Water Splitting. Issue 5 (8th November 2013) - Xie, Mingzheng; Fu, Xuedong; Jing, Liqiang; Luan, Peng; Feng, Yujie; Fu, Honggang
<x xml:space="preserve">Abstract</x> Different mole ratios of TiO2/BiVO4 nanocomposites with effective contacts have are fabricated by putting BiVO4 nanoparticles into the TiO2 sol, followed by thermal treatment at 450 °C. Based on the transient‐state surface photovoltage responses and the atmosphere‐controlled steady‐state surface photovoltage spectra, it is concluded that the photogenerated charge carriers in the TiO2/BiVO4 nanocomposite with a proper mole ratio (5%) display much longer lifetime and higher separation than those in the BiVO4 alone. This is responsible for the unexpected activity for photoelectrochemical oxidation of water, for photocatalytic production of H2, and for photocatalytic degradation of phenol as a model pollutant under visible irradiation. Moreover, it is suggested that the prolonged lifetime and increased separation of photogenerated charges in the fabricated TiO2/BiVO4 nanocomposite is attributed to the unusual spatial transfer of visible‐excited high‐energy electrons of BiVO4 to TiO2. This work will provide feasible routes to synthesize visible‐light responsive nanomaterials for efficient solar utilization.